2020
DOI: 10.1590/1980-0037.2020v22e57958
|View full text |Cite
|
Sign up to set email alerts
|

Effect of small-sided games with manipulation of small targets on the perceived exertion and tactical and technical performance of college soccer players

Abstract: The purpose of this study was to compare the tactical and technical performance and perceived exertion of college soccer players in small-sided games through the manipulation of small targets. Twenty players divided into four teams, played 5x5 games (25x20 m) with one and two small targets on different days. Games were divided into three four-minute times, with two-minute intervals between bouts. Perceived exertion and technical-tactical variables were evaluated using Ball Transmission Speed (ball received/bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, Gonet et al (2020) observed that there was no variation of the RPE in university players in 1G and 2G SSGs. Halouani et al (2014), Brandes et al (2017), andBrandes et al (2012) also did not find a significant difference in PSE values when analyzing 1G, 2G, and SZ SSGs.…”
Section: Physical Performancementioning
confidence: 83%
See 1 more Smart Citation
“…However, Gonet et al (2020) observed that there was no variation of the RPE in university players in 1G and 2G SSGs. Halouani et al (2014), Brandes et al (2017), andBrandes et al (2012) also did not find a significant difference in PSE values when analyzing 1G, 2G, and SZ SSGs.…”
Section: Physical Performancementioning
confidence: 83%
“…One way to quantify the technical-tactical performance of football players is through the Team Sport Assessment Procedure Protocol (TSAP) (Clemente et al, 2014;Brandes et al, 2017;Gonet et al, 2020). This protocol uses the following indices: game volume, efficiency index, performance score, and attacks with the ball (see table 5) (Gréhaigne et al, 1997(Gréhaigne et al, , 2005.…”
Section: Technical and Tactical Performancementioning
confidence: 99%